2004
DOI: 10.1108/07363760410558663
|View full text |Cite
|
Sign up to set email alerts
|

Consumer ethnocentrism and willingness to buy domestic products in a developing country setting: testing moderating effects

Abstract: Previous studies conducted in developed countries have demonstrated that ethnocentric consumers are more willing to buy domestic products. This study investigates the moderating roles of quality judgment of domestic products and conspicuous consumption (CC) in the relationship between consumer ethnocentrism and willingness to buy domestic products (WBD) in the context of a developing country, namely the People's Republic of China. The results support the hypothesis that the impact of ethnocentrism on consumer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
314
1
25

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(352 citation statements)
references
References 50 publications
12
314
1
25
Order By: Relevance
“…Teo ve arkadaşları (2011) Malezyalı örneklem üzerinde yaptıkları çalışmada ölçeğin iki boyutlu bir yapı sergilediği sonucuna ulaşmışlardır. Wang ve Chen (2004) de Çin'de yaptıkları çalışmada ölçeğin dört boyutlu bir yapı sergilediği sonucuna ulaşmışlardır.…”
Section: Tablo 2 Katılımcıların Demografik öZellikleri (N=363)unclassified
“…Teo ve arkadaşları (2011) Malezyalı örneklem üzerinde yaptıkları çalışmada ölçeğin iki boyutlu bir yapı sergilediği sonucuna ulaşmışlardır. Wang ve Chen (2004) de Çin'de yaptıkları çalışmada ölçeğin dört boyutlu bir yapı sergilediği sonucuna ulaşmışlardır.…”
Section: Tablo 2 Katılımcıların Demografik öZellikleri (N=363)unclassified
“…Other researchers have further concluded that this preference for local representatives of the brand is conditioned not only by the fact that the public might sense a greater degree of identification with the famous personage, but also by the existence of a high degree of 'consumer ethnocentrism' among Chinese consumers (Klein, Ettenson, Krishnan, 2006;Klein, 2002;Liu, Murphy, Li & Liu, 2007;Orth & Girbasova, 2003;Wang & Chen, 2004;Wong, Polonsky & Garma, 2008). The construct of ethnocentrism describes the tendency of people to reject people who are culturally dissimilar, and at the same time to favor those who are more like themselves.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Many companies in those sectors seek to arouse consumers' ethnocentricity and thereby build emotional links with them (Hong & Schweitzer, 1996). Chinese consumers can thus find themselves facing a conflict between ethnocentrism and ostentatious or conspicuous consumption, where the latter often wins out (Wang & Chen, 2004;Podoshe, Li & Zhang, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Consumer Ethnocentrism is the tendency of consumers to accept or reject foreign-made products (Sciffman, et al, 2008). The previous researches have shown that in developing countries, consumers assume that products made by local producers are not as good as imported products (Barta, et al, 2000 andChen 2004). Local shoe entrepreneurs and the government can use consumer ethnocentrism as one of local shoe marketing strategies.…”
Section: Consumer Ethnocentrismmentioning
confidence: 99%